Electron spectroscopic studies of vapor-deposited Co layers on MoO3 surfaces - Probst, Marc; Voß, Michael; Denecke, Reinhard; Viscido, L.; Heras, José M.; Borgmann, Dieter; Steinrück, Hans-Peter (Journal of Electron Spectroscopy and Related Phenomena, 2001)
The modification of polycrystalline MoO surfaces by vapor-deposited Co atoms was studied by means of X-ray photoelectron spectroscopy (XPS). Thin MoO layers react with evaporated Co atoms already at 90 K. At 300 K this process proceeds with a significantly higher reaction rate. Besides the Mo 3d signal, two new signals are observed in the Mo 3d XP spectra, which are assigned to Mo and Mo. Cobalt is initially oxidized to Co in the surface layer, but with increasing evaporation time the Co intensity steadily increases. During evaporation at a substrate temperature of 800 K, after an initial increase, a steady state of the Mo and Mo intensities develops. Thereafter at a constant evaporation rate no significant variations of the concentrations are detected within the escape depth of the photoelectrons. This behavior is attributed to interdiffusion processes from the surface and interface layers into the bulk. A satisfying fit of the Mo 3d spectra can only be obtained, when an additional Mo species is assumed, which is assigned to a cobalt molybdate.